2016
DOI: 10.1016/j.ijbiomac.2016.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Venom peptides cathelicidin and lycotoxin cause strong inhibition of Escherichia coli ATP synthase

Abstract: Venom peptides are known to have strong antimicrobial activity and anticancer properties. King cobra cathelicidin or OH-CATH (KF-34), banded krait cathelicidin (BF-30), wolf spider lycotoxin I (IL-25), and wolf spider lycotoxin II (KE-27) venom peptides were found to strongly inhibit E. coli membrane bound F1Fo ATP synthase. The potent inhibition of wild-type E. coli in comparison to the partial inhibition of null E. coli by KF-34, BF-30, Il-25, or KE-27 clearly links the bactericidal properties of these venom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…As for the other groups, reports indicate their antibacterial character [14]. What is very interesting is that the composition of F2 fraction is quite similar to F1, although there is no LAAOs but there are SVMPs and, more importantly, cathelicidin-like antimicrobial peptides, which have a wide spectrum of antibacterial activity and high efficiency [15,16]. Despite this, the F1 fraction did not show any antibacterial properties in our tests.…”
Section: Discussionmentioning
confidence: 49%
“…As for the other groups, reports indicate their antibacterial character [14]. What is very interesting is that the composition of F2 fraction is quite similar to F1, although there is no LAAOs but there are SVMPs and, more importantly, cathelicidin-like antimicrobial peptides, which have a wide spectrum of antibacterial activity and high efficiency [15,16]. Despite this, the F1 fraction did not show any antibacterial properties in our tests.…”
Section: Discussionmentioning
confidence: 49%
“…The variety and spatial positioning of functional groups of inhibitors is one of the main reasons behind complete or partial inhibition of enzymes in general and ATP synthase in particular [57]. In previous studies, numerous instances of variable maximal inhibition of ATP synthase have been observed where wild-type or mutant enzymes were partially or incompletely inhibited by phytochemicals, peptides, NBD-Cl, NaN 3 , AlCl 3 , or ScCl 3 [5, 49, 55, 58, 59]. …”
Section: Discussionmentioning
confidence: 99%
“…If traced back, our application allows detection of differential peptide profiles, providing a robust tool to discriminate not only strain-specific peptides, but true intraspecies differences among a set of biological replicates or even microorganism-phenotype variations such as those occurring between biofilm and planktonic populations. In this regard, the negative effect of certain peptide families on bacteria through different mechanisms is well known [55,56]. In this regard, our pipeline will just provide a candidate peptide list, but experimental approaches such as MS/MS experiments will never detect peptides that are inhibiting own bacterial growth.…”
Section: Resultsmentioning
confidence: 99%